Answered

Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Question 2 (4 points)

Write the equation of the quadratic function in vertex and standard form whose vertex is at [tex]\((-1, 6)\)[/tex] and that passes through [tex]\((2, 24)\)[/tex].


Sagot :

To find the equation of the quadratic function in both vertex and standard form given that the vertex is at [tex]\((-1, 6)\)[/tex] and the parabola passes through the point [tex]\((2, 24)\)[/tex], we can follow these steps:

### Step-by-Step Solution:

#### 1. Understanding the Vertex Form of a Quadratic Function:
The vertex form of a quadratic function is:

[tex]\[ y = a(x - h)^2 + k \][/tex]

where [tex]\((h, k)\)[/tex] is the vertex of the parabola. Here, the vertex [tex]\((h, k)\)[/tex] is given as [tex]\((-1, 6)\)[/tex], so [tex]\(h = -1\)[/tex] and [tex]\(k = 6\)[/tex].

#### 2. Plugging the Vertex into the Equation:
Substituting the vertex values into the vertex form equation, we get:

[tex]\[ y = a(x - (-1))^2 + 6 \][/tex]
[tex]\[ y = a(x + 1)^2 + 6 \][/tex]

#### 3. Using the Given Point to Find [tex]\(a\)[/tex]:
We know that the function passes through the point [tex]\((2, 24)\)[/tex]. Substituting [tex]\(x = 2\)[/tex] and [tex]\(y = 24\)[/tex] into the equation, we get:

[tex]\[ 24 = a(2 + 1)^2 + 6 \][/tex]
[tex]\[ 24 = a \cdot 3^2 + 6 \][/tex]
[tex]\[ 24 = 9a + 6 \][/tex]

Solving for [tex]\(a\)[/tex]:

[tex]\[ 24 - 6 = 9a \][/tex]
[tex]\[ 18 = 9a \][/tex]
[tex]\[ a = 2 \][/tex]

So, we have found that [tex]\(a = 2\)[/tex].

#### 4. Writing the Vertex Form:
Now that we have [tex]\(a = 2\)[/tex], [tex]\(h = -1\)[/tex], and [tex]\(k = 6\)[/tex], the vertex form of the quadratic function is:

[tex]\[ y = 2(x + 1)^2 + 6 \][/tex]

#### 5. Converting Vertex Form to Standard Form:
The standard form of a quadratic function is:

[tex]\[ y = ax^2 + bx + c \][/tex]

To convert [tex]\( y = 2(x + 1)^2 + 6 \)[/tex] to standard form, we need to expand it:

[tex]\[ y = 2(x + 1)^2 + 6 \][/tex]
[tex]\[ y = 2(x^2 + 2x + 1) + 6 \][/tex]
[tex]\[ y = 2x^2 + 4x + 2 + 6 \][/tex]
[tex]\[ y = 2x^2 + 4x + 8 \][/tex]

So, the quadratic function in standard form is:

[tex]\[ y = 2x^2 + 4x + 8 \][/tex]

#### Summary:
- Vertex Form: [tex]\( y = 2(x + 1)^2 + 6 \)[/tex]
- Standard Form: [tex]\( y = 2x^2 + 4x + 8 \)[/tex]

These are the equations of the quadratic function that satisfy the given conditions.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.